2013
DOI: 10.1002/kin.20756
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nucleophilic Substitution Reactions of O,O‐Diethyl 2,4‐dinitrophenyl Phosphate and Thionophosphate Triesters

Abstract: The reactions of the title compounds with phenoxides, secondary alicyclic (SA) amines, and pyridines, in 44 wt% ethanol-water, at 25 • C and an ionic strength of 0.2 M, were subjected to kinetic and product studies. From analytical techniques (HPLC and NMR), two pathways were detected (nucleophilic attack at the phosphoryl center and at the C-1 aromatic carbon) for the reactions of all the nucleophiles with the phosphate (2) and for the pyridinolysis of the thionophosphate (1). Only aromatic nucleophilic subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Recently the "thio effect" (i.e., the effect caused by exchanging the P=O by a P=S bond in OPs) became a matter of interest in reactions with organophosphates, where the solvent effect and the nature of nucleophiles were evaluated. 16,17 In this sense, Aguayo et al 6 studied the reaction of several pyridine and phenol derivatives with diethyl 2,4-dinitrophenylphosphate (DEDNPP) and diethyl 2,4-dinitrophenylthiophosphate (DEDNPSP). The results showed nucleophilic attacks at the aromatic carbon and phosphorus in different proportions, for pyridine nucleophiles.…”
Section: Are Imidazoles Versatile or Promiscuous In Reactions With Ormentioning
confidence: 99%
See 3 more Smart Citations
“…Recently the "thio effect" (i.e., the effect caused by exchanging the P=O by a P=S bond in OPs) became a matter of interest in reactions with organophosphates, where the solvent effect and the nature of nucleophiles were evaluated. 16,17 In this sense, Aguayo et al 6 studied the reaction of several pyridine and phenol derivatives with diethyl 2,4-dinitrophenylphosphate (DEDNPP) and diethyl 2,4-dinitrophenylthiophosphate (DEDNPSP). The results showed nucleophilic attacks at the aromatic carbon and phosphorus in different proportions, for pyridine nucleophiles.…”
Section: Are Imidazoles Versatile or Promiscuous In Reactions With Ormentioning
confidence: 99%
“…Moreover, the attack at phosphorus was always majority for DEDNPP in contrast to DEDNPSP. 6 Rougier et al 18 studied the reaction of fenitrothion (thiophosphate structurally related to parathion) with some α-nucleophiles and observed that nitrogenated nucleophiles attack the phosphorus and aliphatic carbons. Indeed, there is no straightforward mechanistic trend of OPs containing P=O or its analogue with P=S and this comprehensive understanding related to structure is essential since this is one of the most valuable tools for destroying these compounds, leading to knowingly less toxic substances.…”
Section: Are Imidazoles Versatile or Promiscuous In Reactions With Ormentioning
confidence: 99%
See 2 more Smart Citations
“…One study shows that the reactiono fs econdary amines with the OP simulant diethyl-2,4-dinitrophenylphosphate (DEDNPP) occurs exclusively at the phosphorusa tom ( Figure 1, path c), but for the thio analogue, that is, DEDNPSP, this nucleophilic attack can happena tb otht he phosphorus and aromatic carbona toms (Figure 1, paths aa nd b). [3] In contrast, with the pesticidef enitrothion, primarya minesn ot only react at the phosphorus atom but also at the aliphatic carbon atom (Figure 1, pathsd and e). [4] Moreover,t he pesticide paraoxon was evaluated with various secondary amines, and it underwenta ttack solely at the phosphorus center ( Figure 1, path f).…”
Section: Introductionmentioning
confidence: 99%